A Profibrotic Phenotype in Naïve and in Fibrotic Lung Myofibroblasts Is Governed by Modulations in Thy-1 Expression and Activation. (29th May 2018) - Cohen, Pazit Y.; Breuer, Raphael; Wallach-Dayan, Shulamit B.
Abstract : Lung fibrosis is characterized by abnormal accumulation of Thy-deficient fibroblasts in the interstitium of the alveolar space. We have previously shown in bleomycin-treated chimeric Thy1-deficient mice with wild-type lymphocytes that Thy1-deficient fibroblasts accumulate and promote fibrosis and an "inflammation-free" environment. Here, we aimed to identify the critical effects of Thy1, or the absence of Thy1, in lung myofibroblast profibrotic functions, particularly proliferation and collagen deposition. Using specific Thy1 siRNA in Thy1-positive cells, Thy1 knockout cells, Thy1 cDNA expression vector in Thy1-deficient cells, and Thy1 cross-linking, we evaluated cell proliferation (assessed by cell mass and BrdU uptake), differentiation (using immunofluorescence), and collagen deposition (using Sircol assay). We found that myofibroblast Thy1 cross-linking and genetic manipulation modulate cell proliferation and expression of Fgf (fibroblast growth factor) and Angtl (angiotensin) receptors (using qPCR) that are involved in myofibroblast proliferation, differentiation, and collagen deposition. In conclusion, lung myofibroblast downregulation of Thy1 expression is critical to increase proliferation, differentiation, and collagen deposition.